Silver powder and preparation method and application thereof

By introducing high adhesion resin as a coating agent in the preparation of silver powder, the problem of difficult balance of adhesion and printing properties during the fine-grid silver paste printing process on the back of the TOPCon battery is solved, and high adhesion and fluency are achieved, avoiding the The grid lines fall off and break the grid improve printing quality.

CN119114959AActive Publication Date: 2024-12-13HA SHEN TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411329403.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-13
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The fine-grid silver paste on the back of the existing TOPCon battery is prone to problems of gate lines falling off and gate breaking during the printing process, making it difficult to balance adhesion and printing properties, resulting in poor printing.

Method used

By introducing a high adhesion resin as a coating component during the preparation of silver powder, polar groups of thermoplastic acrylate, hydrogenated rosin resin and polyvinyl butyral resin are adsorbed on the surface of silver powder to improve the connection between silver powder and adhesion, and closely bond with the surface of the cell.

Benefits of technology

It effectively improves the adhesion of the fine grid on the back of the TOPCon, reduces the viscosity of the slurry, improves printing fluency, avoids the phenomenon of grid lines falling off and breaking during the printing process, and improves printing quality.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses silver powder and a preparation method and application thereof, and belongs to the technical field of silver powder. The preparation method of the silver powder comprises the steps that a silver ion solution, a reducing solution and a dispersing agent solution are mixed to react, and a reaction solution is obtained; carrying out solid-liquid separation on the reaction liquid, mixing the solid with a coating agent solution, and drying; the coating agent solution comprises at least one of lauric acid, sodium laurate, a silane coupling agent, oleic acid, lauric acid, stearic acid, palmitic acid and benzotriazole and at least one of acrylic resin, rosin resin and polyvinyl butyral. Resin with high adhesive force is introduced in the silver powder preparation process and serves as a coating agent component, the adhesive force of the TOPCon back fine grid slurry printed on a silicon wafer can be improved, the phenomenon that grid lines of the back slurry fall off is avoided, meanwhile, it can be ensured that the viscosity of the slurry is low, the printing smoothness is improved, and the service life of the slurry is prolonged. And the problem of a large number of broken gates in the printing process is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silver powder, and in particular to silver powder and a preparation method and application thereof. Background Art

[0002] TOPCon cells are also called tunnel oxide passivated contacts. This cell is made by preparing a 1nm to 2nm tunnel oxide layer on the back, and then depositing a layer of doped polysilicon. The two together form a passivated contact structure. The conductive silver paste is printed on the silicon wafer surface by screen printing on both the front and back of the TOPCon cell. The entire printing process is divided into four processes: one is to print the back main grid, and then dry it; the second is to print the back fine grid, and then dry it; the third is to print the front main grid, and then dry it; the fourth is to print the front fine grid, and then sinter it. Between the second and third processes, the TOPCon back fine grid is in direct contact with the printing machine, and the grid line is prone to fall off, so the back conductive silver paste needs to have good adhesion.

[0003] The existing TOPCon back-side fine grid slurry mainly uses resin combined with solvents, leveling agents, etc. to make an organic carrier, and then mixes the organic carrier, glass powder and silver powder to make silver paste to improve the adhesion and printability of the slurry. However, it is usually difficult to balance the adhesion and printing problems through this solution. Good adhesion requires the addition of a large amount of resin, but too much resin will cause the slurry viscosity to be too high and the printing to be poor.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a silver powder and a preparation method and application thereof, so as to solve or improve the above technical problems.

[0006] The present invention can be implemented like this:

[0007] In a first aspect, the present invention provides a method for preparing silver powder, comprising the following steps:

[0008] The silver ion solution, the reducing solution and the dispersant solution are mixed and reacted to obtain a reaction solution; the reaction solution is solid-liquid separated and the solid is collected;

[0009] mixing the solid with the coating agent solution and drying;

[0010] The coating agent solution includes a first solute and a second solute, wherein the first solute includes at least one of lauric acid, sodium laurate, silane coupling agent, oleic acid, lauric acid, stearic acid, palmitic acid and benzotriazole; and the second solute includes at least one of acrylic resin, rosin resin and polyvinyl butyral resin.

[0011] In an optional embodiment, the second solute is at least one of thermoplastic acrylate, hydrogenated rosin resin and polyvinyl butyral resin.

[0012] In an optional embodiment, in the coating agent solution, the content of the first solute is 0.01 g / mL to 0.05 g / mL, and the content of the second solute is 0.01 g / mL to 0.05 g / mL.

[0013] In an optional embodiment, in the coating agent solution, the solvent includes at least one of ethanol, isopropanol and acetone.

[0014] In an optional embodiment, the concentration of silver ions in the silver ion solution is 0.1 mol / L to 5 mol / L;

[0015] In an optional embodiment, the concentration of silver ions in the silver ion solution is 0.5 mol / L to 3 mol / L;

[0016] In an alternative embodiment, the silver ion solution is obtained by mixing silver nitrate with water.

[0017] In an optional embodiment, the concentration of the reducing agent in the reducing solution is 0.2 mol / L to 2 mol / L;

[0018] In an optional embodiment, the concentration of the reducing agent in the reducing solution is 0.4 mol / L to 1.5 mol / L.

[0019] In an alternative embodiment, the reducing agent comprises at least one of glucose, hydrazine hydrate, sodium borohydride, potassium borohydride, ascorbic acid, urea, formaldehyde and isoascorbic acid.

[0020] In an optional embodiment, the content of the dispersant in the dispersant solution is 0.01 g / mL to 1 g / mL.

[0021] In an optional embodiment, the content of the dispersant in the dispersant solution is 0.05 g / mL to 0.5 g / mL.

[0022] In an alternative embodiment, the dispersant in the dispersant solution includes at least one of polyvinyl pyrrolidone, maleic acid, cyclodextrin, fumaric acid, gelatin, malic acid, gum arabic, polyacrylamide and oleic acid.

[0023] In an optional embodiment, the reaction temperature of the silver ion solution, the reducing solution and the dispersant solution is 15° C. to 50° C., and the reaction time is 5 min to 20 min;

[0024] In an optional embodiment, the molar ratio of the reducing agent in the reducing solution to the silver ions in the silver ion solution is 0.5:1 to 4:1, and the mass of the dispersant in the dispersant solution is 1% to 40% of the mass of the silver source providing silver ions in the silver ion solution.

[0025] In an optional embodiment, the molar ratio of the reducing agent in the reducing solution to the silver ions in the silver ion solution is 0.5:1 to 2:1, and the mass of the dispersant in the dispersant solution is 10% to 30% of the mass of the silver source providing silver ions in the silver ion solution.

[0026] In an optional embodiment, the silver ion solution and the reducing solution are both introduced into the dispersant solution at a flow rate of 5 mL / min to 50 mL / min.

[0027] In an optional embodiment, the reaction is carried out at a stirring speed of 200 rpm to 250 rpm.

[0028] In an optional embodiment, the mass ratio of solid to coating agent solution is 1:1 to 1:2.

[0029] In an optional embodiment, the solid and the coating agent solution are mixed at a stirring speed of 100 rpm to 800 rpm for 5 min to 60 min.

[0030] In an optional embodiment, the drying temperature after the solid and the coating agent solution are mixed is 35° C. to 60° C., and the drying time is 1 h to 5 h.

[0031] In an optional embodiment, the solid is further washed before being mixed with the coating agent solution.

[0032] In an optional embodiment, the solid is washed with deionized water and ethanol in sequence until the conductivity of the washing liquid is ≤20 μs / cm.

[0033] In a second aspect, the present invention provides a silver powder prepared by the preparation method of any one of the aforementioned embodiments.

[0034] In an optional embodiment, the silver powder has a D 50 It is 1.2μm~1.8μm.

[0035] In an optional embodiment, the tap density of the silver powder is 5.5 g / cm 3 ~6.3g / cm 3 .

[0036] In an optional embodiment, the specific surface area of ​​the silver powder is 0.35 m 2 / g~0.75m 2 / g.

[0037] In an optional embodiment, the burnout of the silver powder is 0.5 wt % to 1 wt %.

[0038] In a third aspect, the present invention provides a silver paste, wherein raw materials for preparing the silver paste include an organic carrier, glass powder and the silver powder of the aforementioned embodiment.

[0039] In an optional embodiment, the raw materials for preparing the silver paste include, by weight, 86 to 90 parts of silver powder, 8 to 12 parts of an organic vehicle, and 2 to 3 parts of glass powder.

[0040] In a fourth aspect, the present invention provides a TOPCon battery, wherein the silver paste on the back side of the TOPCon battery is the silver paste of the aforementioned embodiment.

[0041] The beneficial effects of the present invention include:

[0042] By introducing a resin with high adhesion during the preparation of silver powder and using the resin as a coating agent component, the adhesion of the TOPCon back-side fine grid paste after printing on the silicon wafer can be improved, avoiding the phenomenon of grid lines falling off on the back side of the paste. At the same time, it can ensure that the viscosity of the paste is low, improve printing smoothness, and avoid the problem of a large number of broken grids during the printing process.

[0043] Among them, thermoplastic acrylate, hydrogenated rosin resin and polyvinyl butyral resin contain a large amount of polar groups, carboxyl groups or hydroxyl groups, and the polar groups can be firmly adsorbed on the surface of silver powder. After the silver powder coated with the above resin is prepared into slurry, the silver powder and the silver powder can be connected together through the long chain effect of the resin. At the same time, the polar groups can also be firmly adsorbed on the surface of the battery cell, ensuring the adhesion of the fine grid. After the silver powder that has not been coated with the above resin is made into slurry, the silver powder and the silver powder particles cannot be effectively connected together, so the fine grid will be damaged under very small external force. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0045] The silver powder provided by the present invention and its preparation method and application are described in detail below.

[0046] The present invention provides a method for preparing silver powder, comprising the following steps:

[0047] The silver ion solution, the reducing solution and the dispersant solution are mixed and reacted to obtain a reaction solution; the reaction solution is solid-liquid separated and the solid is collected;

[0048] mixing the solid with the coating agent solution and drying;

[0049] The coating agent solution includes a first solute and a second solute, wherein the first solute includes at least one of lauric acid, sodium laurate, silane coupling agent, oleic acid, lauric acid, stearic acid, palmitic acid and benzotriazole; and the second solute includes at least one of acrylic resin, rosin resin and polyvinyl butyral resin.

[0050] In some preferred embodiments, the second solute is at least one of thermoplastic acrylate, hydrogenated rosin resin and polyvinyl butyral resin.

[0051] The present invention introduces a resin with high adhesion during the preparation of silver powder and uses the resin as a coating agent component, thereby improving the adhesion of TOPCon back side fine grid slurry after printing on a silicon wafer, avoiding the phenomenon of grid line falling off of the back side slurry, and ensuring that the slurry viscosity is low, improving printing smoothness, and avoiding the problem of a large number of broken grids during the printing process.

[0052] Among them, thermoplastic acrylate, hydrogenated rosin resin and polyvinyl butyral resin contain a large amount of polar groups, carboxyl groups or hydroxyl groups, and the polar groups can be firmly adsorbed on the surface of silver powder. After the silver powder coated with the above resin is prepared into slurry, the silver powder and the silver powder can be connected together through the long chain effect of the resin. At the same time, the polar groups can also be firmly adsorbed on the surface of the battery cell, ensuring the adhesion of the fine grid. After the silver powder that has not been coated with the above resin is made into slurry, the silver powder and the silver powder particles cannot be effectively connected together, so the fine grid will be damaged under very small external force.

[0053] It should be noted that if the above resin components are directly added during the reaction process, the resin will not be dissolved and normal production and preparation cannot be carried out.

[0054] In some optional embodiments, the concentration of silver ions in the silver ion solution can be 0.1mol / L to 5mol / L, such as 0.1mol / L, 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, 4mol / L, 4.5mol / L or 5mol / L, etc., or other values ​​within the range of 0.1mol / L to 5mol / L. In some typical embodiments, the concentration of silver ions in the silver ion solution is 0.5mol / L to 3mol / L.

[0055] The silver ion solution can be obtained by mixing a silver source (such as silver nitrate) with water. In addition, it is not excluded that the silver source is at least one of silver sulfate, silver carbonate, silver acetate, silver lactate, silver bromide, silver iodide, silver phosphate and silver stearate.

[0056] In some optional embodiments, the concentration of the reducing agent in the reducing solution can be 0.2mol / L to 2mol / L, such as 0.2mol / L, 0.5mol / L, 0.8mol / L, 1mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L or 2mol / L, etc., or other values ​​within the range of 0.2mol / L to 2mol / L. In some typical embodiments, the concentration of the reducing agent in the reducing solution is 0.4mol / L to 1.5mol / L.

[0057] By way of example, the reducing agent may include at least one of glucose, hydrazine hydrate, sodium borohydride, potassium borohydride, ascorbic acid, urea, formaldehyde, and isoascorbic acid.

[0058] In some optional embodiments, the content of the dispersant in the dispersant solution is 0.01 g / mL to 1 g / mL, and can be 0.01 g / mL, 0.05 g / mL, 0.1 g / mL, 0.2 g / mL, 0.5 g / mL, 0.8 g / mL or 1 g / mL, etc., or other values ​​within the range of 0.01 g / mL to 1 g / mL. In some more typical embodiments, the content of the dispersant in the dispersant solution is 0.05 g / mL to 0.5 g / mL, and further 0.06 g / mL to 0.1 mg / mL.

[0059] By way of example, the dispersant in the dispersant solution may include at least one of polyvinyl pyrrolidone, maleic acid, cyclodextrin, fumaric acid, gelatin, malic acid, gum arabic, polyacrylamide, and oleic acid.

[0060] In some optional embodiments, the reaction temperature of the silver ion solution, the reducing solution and the dispersant solution can be 15°C to 50°C, such as 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C, etc., or other values ​​within the range of 15°C to 50°C.

[0061] The reaction time of the silver ion solution, the reducing solution and the dispersant solution can be 5 min to 20 min, such as 5 min, 10 min, 15 min or 20 min, etc., or other values ​​within the range of 5 min to 20 min.

[0062] In some optional embodiments, the molar ratio of the reducing agent in the reducing solution to the silver ions in the silver ion solution is 0.5:1 to 4:1, such as 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1, etc., and can also be other values ​​in the range of 0.5:1 to 4:1. In some more typical embodiments, the molar ratio of the reducing agent in the reducing solution to the silver ions in the silver ion solution is 0.5:1 to 2:1, and further 0.8:1 to 1.5:1.

[0063] The mass of the dispersant in the dispersant solution is 1% to 40% of the mass of the silver source providing silver ions in the silver ion solution, such as 1%, 2%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35% or 40%, etc., and can also be other values ​​within the range of 1% to 40%. In some typical embodiments, the mass of the dispersant in the dispersant solution is 10% to 30% of the mass of the silver source providing silver ions in the silver ion solution, and further 19.6% to 29.4%.

[0064] The solvent in the silver ion solution, reducing solution and dispersant solution is water.

[0065] In some embodiments, the silver ion solution and the reducing solution are both introduced into the dispersant solution at a flow rate of 5 mL / min to 50 mL / min (e.g., 5 mL / min, 10 mL / min, 15 mL / min, 20 mL / min, 25 mL / min, 30 mL / min, 35 mL / min, 40 mL / min, 45 mL / min, or 50 mL / min, etc.).

[0066] Preferably, the reaction of the silver ion solution, the reducing solution and the dispersant solution is carried out under stirring. The stirring speed can be 200 rpm to 250 rpm, such as 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm or 250 rpm.

[0067] Under the above conditions, the silver ion solution and the reducing solution can be reacted uniformly and sufficiently.

[0068] After the reaction is completed, the reaction solution obtained by the reaction is subjected to solid-liquid separation, and the separated solid is collected and washed.

[0069] In some optional embodiments, the solid may be washed with deionized water and ethanol in sequence until the conductivity of the washing solution is ≤20 μs / cm.

[0070] Furthermore, the washed solid is mixed with a coating agent solution.

[0071] In some optional embodiments, the mass ratio of the solid to the coating agent solution can be 1:1 to 1:2, such as 1:1, 1:1.5 or 1:2.

[0072] In the coating agent solution, the content of the first solute is 0.01 g / mL to 0.05 g / mL, such as 0.01 g / mL, 0.02 g / mL, 0.03 g / mL, 0.04 g / mL or 0.05 g / mL, etc., and can also be any other value within the range of 0.01 g / mL to 0.05 g / mL.

[0073] The content of the second solute is 0.01 g / mL to 0.05 g / mL, such as 0.01 g / mL, 0.02 g / mL, 0.03 g / mL, 0.04 g / mL or 0.05 g / mL, etc., and can also be any other value within the range of 0.01 g / mL to 0.05 g / mL.

[0074] Illustratively, the solvent in the coating agent solution may include at least one of ethanol, isopropanol, acetone, and the like.

[0075] In the second solute, if the amount of resin used is too small compared to the solid, it is not conducive to the dispersibility of the silver powder; if the amount of resin used is too large compared to the solid, it is easy to cause the silver powder to be too sticky, affecting the printability of the slurry.

[0076] The solid and the coating agent solution are mixed at a stirring speed of 100 rpm to 800 rpm (such as 100 rpm, 200 rpm, 400 rpm, 600 rpm or 800 rpm, etc.) for 5 min to 60 min (such as 5 min, 10 min, 20 min, 30 min, 40 min, 50 min or 60 min, etc.).

[0077] Mixing under the above conditions can make the coating more uniform.

[0078] In some optional embodiments, the drying temperature after the solid and the coating agent solution are mixed is 35°C to 60°C (such as 35°C, 40°C, 45°C, 50°C, 55°C or 60°C, etc.), and the drying time is 1h to 5h (such as 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, etc.).

[0079] As mentioned above, the preparation method of the silver powder provided by the present invention is simple in process, easy to operate, time-saving and labor-saving.

[0080] The energy consumption is low, the silver powder yield is high and the spherical morphology of the silver powder can be effectively maintained.

[0081] Correspondingly, the present invention also provides a silver powder, which is prepared by the above preparation method.

[0082] In some optional embodiments, the silver powder has a D 50 It is 1.2μm~1.8μm.

[0083] In some optional embodiments, the tap density of the silver powder is 5.5 g / cm 3 ~6.3g / cm 3 .

[0084] In some optional embodiments, the specific surface area of ​​the silver powder is 0.35 m 2 / g~0.75m 2 / g.

[0085] In some optional embodiments, the burnout of the silver powder is 0.5 wt % to 1 wt %.

[0086] The silver powder particles provided by the present invention have good morphology and high specific surface area, which is beneficial to improving sintering activity and sintering shrinkage rate.

[0087] In addition, the present invention also provides a silver paste, and the raw materials for preparing the silver paste include an organic carrier, glass powder and the above-mentioned silver powder.

[0088] In some optional embodiments, the raw materials for preparing the silver paste include, by weight, 86 to 90 parts of silver powder, 8 to 12 parts of organic carrier, and 2 to 3 parts of glass powder.

[0089] The amount of silver powder used may be 86 parts, 86.5 parts, 87 parts, 87.5 parts, 88 parts, 88.5 parts, 89 parts, 89.5 parts or 90 parts, etc., or other values ​​within the range of 86 to 90 parts.

[0090] The amount of the organic carrier can be 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 10.5 parts, 11 parts, 11.5 parts or 12 parts, etc., and can also be other values ​​within the range of 8 to 12 parts.

[0091] The amount of glass powder used can be 2 parts, 2.5 parts, 3 parts, etc., or other values ​​within the range of 2 parts to 3 parts.

[0092] The viscosity of the above silver paste is about 100Pa·s~180Pa·s (measurement conditions: Brookfield DV2T viscometer, rotation speed 10rpm), which has good printing smoothness and avoids or improves the risk of a large number of broken grids during the printing process; at the same time, the paste also has good adhesion and can improve the phenomenon of grid line falling off.

[0093] As mentioned above, after the silver powder provided by the present invention is prepared into a slurry, it can be smoothly printed on a screen below 10μm. The printed grid lines have excellent adhesion after drying, without falling off (3M tape after grid lines are dried, 0 falling off) and smooth printing without broken grids.

[0094] Furthermore, the present invention also provides a TOPCon battery, the back silver paste of the TOPCon battery is the above silver paste.

[0095] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0096] Example 1

[0097] This embodiment provides a method for preparing silver powder, comprising the following steps:

[0098] S1: Use a peristaltic pump to uniformly add 300 mL of silver ion solution and 400 mL of reducing solution into 300 mL of dispersant solution at a rate of 10 mL / min, with a stirring speed of 200 rpm, a process temperature of 40°C, and a reaction time of 10 min.

[0099] The silver ion solution is obtained by mixing silver nitrate with deionized water, and the concentration of silver ions in the silver ion solution is 2 mol / L. The reducing solution is obtained by mixing glucose with deionized water, and the concentration of glucose in the reducing solution is 1.2 mol / L. The dispersant solution is obtained by mixing 25 g of polyvinyl pyrrolidone K30 with 300 mL of deionized water.

[0100] That is, the molar ratio of the reducing agent in the reducing solution to the silver ions in the silver ion solution is 0.8:1, and the mass of the dispersant in the dispersant solution is 24.5% of the mass of the silver source providing silver ions in the silver ion solution.

[0101] S2: After the reaction is completed, the obtained reaction solution is filtered to collect the solid; the solid is washed with deionized water and ethanol respectively until the conductivity of the washing solution is ≤20μS / cm to obtain a wet powder.

[0102] S3: The cleaned wet powder and the coating agent solution were stirred at a mass ratio of 1:1 (stirring speed of 450 rpm) for 10 minutes, then dried (temperature of 40°C, time of 2 hours), sieved, and the obtained silver powder was recorded as A1.

[0103] The coating agent solution was prepared by dissolving 2 g of lauric acid and 2 g of acrylic resin (Mitsubishi BR115) in 100 mL of ethanol.

[0104] The mass yield of the silver powder obtained in this example is 93.02%.

[0105] Example 2

[0106] This embodiment provides a method for preparing silver powder, comprising the following steps:

[0107] S1: Use a peristaltic pump to uniformly add 300 mL of silver ion solution and 500 mL of reducing solution into 300 mL of dispersant solution at a rate of 15 mL / min, with a stirring speed of 220 rpm, a process temperature of 35°C, and a reaction time of 10 min.

[0108] The silver ion solution is obtained by mixing silver nitrate with deionized water, and the concentration of silver ions in the silver ion solution is 2 mol / L. The reducing solution is obtained by mixing ascorbic acid with deionized water, and the concentration of ascorbic acid in the reducing solution is 1.5 mol / L. The dispersant solution is obtained by mixing 30 g of polyacrylamide with 300 mL of deionized water.

[0109] That is, the molar ratio of the reducing agent in the reducing solution to the silver ions in the silver ion solution is 1.25:1, and the mass of the dispersant in the dispersant solution is 29.4% of the mass of the silver source providing silver ions in the silver ion solution.

[0110] S2: After the reaction is completed, the obtained reaction solution is filtered to collect the solid; the solid is washed with deionized water and ethanol respectively until the conductivity of the washing solution is ≤20μS / cm to obtain a wet powder.

[0111] S3: The cleaned wet powder and the coating agent solution were stirred at a mass ratio of 1:1.5 (stirring speed of 550 rpm) for 10 minutes, then dried (temperature of 45°C, time of 1.5 hours), sieved, and the obtained silver powder was recorded as A2.

[0112] The coating agent solution is composed of 2g stearic acid and 2g hydrogenated rosin resin (Eastman 105) was dissolved in 100 mL of ethanol.

[0113] The yield of the silver powder obtained in this example is 92.40%.

[0114] Example 3

[0115] This embodiment provides a method for preparing silver powder, comprising the following steps:

[0116] S1: Use a peristaltic pump to uniformly add 300 mL of silver ion solution and 600 mL of reducing solution into 300 mL of dispersant solution at a rate of 10 mL / min, with a stirring speed of 210 rpm, a process temperature of 25°C, and a reaction time of 15 min.

[0117] The silver ion solution is obtained by mixing silver nitrate with deionized water, and the concentration of silver ions in the silver ion solution is 2 mol / L. The reducing solution is obtained by mixing formaldehyde with deionized water, and the concentration of formaldehyde in the reducing solution is 1.5 mol / L. The dispersant solution is obtained by mixing 20 g of polyacrylamide with 300 mL of deionized water.

[0118] That is, the molar ratio of the reducing agent in the reducing solution to the silver ions in the silver ion solution is 1.5:1, and the mass of the dispersant in the dispersant solution is 19.6% of the mass of the silver source providing silver ions in the silver ion solution.

[0119] S2: After the reaction is completed, the obtained reaction solution is filtered to collect the solid; the solid is washed with deionized water and ethanol respectively until the conductivity of the washing solution is ≤20μS / cm to obtain a wet powder.

[0120] S3: The cleaned wet powder and the coating agent solution were stirred at a mass ratio of 1:1.2 (stirring speed of 600 rpm) for 10 minutes, then dried (temperature of 45°C, time of 3 hours), sieved, and the obtained silver powder was recorded as A3.

[0121] The coating agent solution was prepared by dissolving 2 g of stearic acid and 1.5 g of polyvinyl butyral resin (Kuraray B60HH) in 100 mL of ethanol.

[0122] The yield of the silver powder obtained in this example is 92.25%.

[0123] Example 4

[0124] This embodiment provides a method for preparing silver powder, comprising the following steps:

[0125] S1: Use a peristaltic pump to uniformly add 300 mL of silver ion solution and 500 mL of reducing solution into 300 mL of dispersant solution at a rate of 5 mL / min, with a stirring speed of 230 rpm, a process temperature of 15°C, and a reaction time of 20 min.

[0126] The silver ion solution is obtained by mixing silver nitrate with deionized water, and the concentration of silver ions in the silver ion solution is 0.5 mol / L. The reducing solution is obtained by mixing hydrazine hydrate with deionized water, and the concentration of hydrazine hydrate in the reducing solution is 0.4 mol / L. The dispersant solution is obtained by mixing 5 g of maleic acid with 300 mL of deionized water.

[0127] That is, the molar ratio of the reducing agent in the reducing solution to the silver ions in the silver ion solution is 1.33:1, and the mass of the dispersant in the dispersant solution is 19.6% of the mass of the silver source providing silver ions in the silver ion solution.

[0128] S2: After the reaction is completed, the obtained reaction solution is filtered to collect the solid; the solid is washed with deionized water and ethanol respectively until the conductivity of the washing solution is ≤20μS / cm to obtain a wet powder.

[0129] S3: The cleaned wet powder and the coating agent solution were stirred at a mass ratio of 1:2 (stirring speed of 100 rpm) for 60 minutes, then dried (temperature of 35°C, time of 6 hours), sieved, and the obtained silver powder was recorded as A4.

[0130] The coating agent solution is composed of 2g sodium laurate, 1.0g polyvinyl butyral resin (Kuraray B30HH) and 1g hydrogenated rosin resin ( 3085) was dissolved in 100 mL of ethanol.

[0131] The yield of the silver powder obtained in this example is 91.20%.

[0132] Example 5

[0133] This embodiment provides a method for preparing silver powder, comprising the following steps:

[0134] S1: Use a peristaltic pump to uniformly add 300 mL of silver ion solution and 500 mL of reducing solution into 300 mL of dispersant solution at a rate of 50 mL / min, with a stirring speed of 250 rpm, a process temperature of 50°C, and a reaction time of 5 minutes.

[0135] The silver ion solution is obtained by mixing silver nitrate with deionized water, and the concentration of silver ions in the silver ion solution is 3 mol / L. The reducing solution is obtained by mixing sodium borohydride with deionized water, and the concentration of sodium borohydride in the reducing solution is 2 mol / L. The dispersant solution is obtained by mixing 30 g of cyclodextrin with 300 mL of deionized water.

[0136] That is, the molar ratio of the reducing agent in the reducing solution to the silver ions in the silver ion solution is 1.11:1, and the mass of the dispersant in the dispersant solution is 19.6% of the mass of the silver source providing silver ions in the silver ion solution.

[0137] S2: After the reaction is completed, the obtained reaction solution is filtered to collect the solid; the solid is washed with deionized water and ethanol respectively until the conductivity of the washing solution is ≤20μS / cm to obtain a wet powder.

[0138] S3: The cleaned wet powder and the coating agent solution were stirred at a mass ratio of 1:1 (stirring speed of 800 rpm) for 5 minutes, then dried (temperature of 60°C, time of 1 hour), sieved, and the obtained silver powder was recorded as A5.

[0139] The coating agent solution was prepared by dissolving 2 g of palmitic acid, 1.5 g of acrylic resin (Japan HIPLAAD ER 2602) and 1 g of polyvinyl butyral resin (Kuraray B20H) in 100 mL of ethanol.

[0140] The yield of the silver powder obtained in this example is 92.10%.

[0141] Comparative Example 1

[0142] The difference between this comparative example and Example 1 is that the coating agent solution is obtained by dissolving 2 g of lauric acid and 0.5 g of acrylic resin (Mitsubishi BR115) in 100 mL of ethanol. The obtained product is recorded as B1, with a yield of 93.48% and a burning loss of 0.88 wt%.

[0143] Comparative Example 2

[0144] The difference between this comparative example and Example 1 is that the coating agent solution is obtained by dissolving 2 g of lauric acid and 10 g of acrylic resin (Mitsubishi BR115) in 100 mL of ethanol, and the obtained product is recorded as B2, with a yield of 92.87% and a burning loss of 0.89 wt%.

[0145] Comparative Example 3

[0146] The difference between this comparative example and Example 1 is that the coating agent solution is obtained by dissolving 2 g of lauric acid in 100 mL of ethanol, and the obtained product is recorded as B3, with a yield of 92.87% and a loss on burn of 0.72 wt%.

[0147] Comparative Example 4

[0148] The difference between this comparative example and Example 4 is that the coating agent solution does not contain polyvinyl butyral resin, and the obtained product is recorded as B4, with a yield of 90.2% and a burn loss of 0.76wt%.

[0149] Comparative Example 5

[0150] The difference between this comparative example and Example 1 is that the coating agent solution does not contain acrylic resin, and the obtained product is recorded as B5, with a yield of 92.2% and a burn loss of 0.81wt%.

[0151] ①. The performance of the silver powder obtained in Examples 1 to 5 was tested, and the results are shown in Table 1.

[0152] Table 1 Comparison results of silver powder

[0153] <![CDATA[D 50 (μm)]]> <![CDATA[Tap density (g / cm 3 )]]> <![CDATA[Specific surface area (m 2 / g)]]> Burning loss (wt%) Yield (%) Example 1 1.55 6.23 0.62 0.68 93.02 Example 2 1.66 6.20 0.64 0.59 92.40 Example 3 1.45 5.95 0.45 0.50 92.25 Example 4 1.51 5.50 0.51 0.52 91.20 Example 5 1.58 5.89 0.60 0.56 92.10

[0154] ②. The silver powder obtained in each embodiment and the comparative example is respectively configured with glass powder and an organic carrier to form a slurry. The specific operation is as follows: 528g of silver powder, 13.2g of glass powder and 58.8g of organic carrier are weighed and mixed evenly. After stirring evenly with a homogenizer, they are rolled using a 60E Aikat three-roll mill to make TOPCon back side fine grid slurry, wherein the organic carrier is composed of ethyl cellulose STD-4, SEBS and diethylene glycol butyl ether acetate in a mass ratio of 5:5:90.

[0155] At the same time, a control example was set up: 528g of silver powder (silver powder in comparison example 1), 13.2g of glass powder and 58.8g of organic carrier were weighed and mixed evenly. After stirring evenly with a homogenizer, they were rolled using a 60E Aikat three-roller mill to make TOPCon back fine grid slurry, wherein the organic carrier was composed of acrylic resin BR115, ethyl cellulose STD-4, SEBS and diethylene glycol butyl ether acetate in a mass ratio of 5:5:5:85.

[0156] 3M test: The prepared slurry is screen-printed on a MAXWELL printer, and the printed TOPCon silicon wafer is dried in a drying oven (temperature is 300℃~350℃, time is 30s). 3M tape is adhered to the dried silicon wafer, and gently pressed with fingers to make sure there are no bubbles under the tape. Then the tape is quickly torn off the silicon wafer by hand, and the detachment of the gate line from the silicon wafer is observed. The results are shown in Table 2.

[0157] EL test: The TOPCon sheets after drying are subjected to the following processes, such as printing the main grid and fine grid on the front side, sintering (the temperature of the sintering furnace is between 350℃ and 780℃, the peak temperature is 780℃, and the time is 60s), etc. The sintered sheets are tested for the broken grid condition using EL test equipment, and the results are shown in Table 3.

[0158] Table 2 Comparison results

[0159] 3M fine grid shedding ratio Example 1 0% Example 2 0% Example 3 0% Example 4 0% Example 5 0% Comparative Example 1 8% Comparative Example 2 0% Comparative Example 3 35% Comparative Example 4 30% Comparative Example 5 45% Comparison example 5%

[0160] It can be seen from Table 2 that by introducing the resin into the coating agent solution to coat the silver wet powder, the fine grid can be effectively prevented from falling off. From Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3, if the acrylic resin content is too little (such as Comparative Example 1), 8% of the fine grid will fall off. Only when it reaches a certain content can the fine grid be guaranteed not to fall off.

[0161] Table 3 Comparison results

[0162] EL gate breaking number (roots) Example 1 0 Example 2 0 Example 3 0 Example 4 0 Example 5 0 Comparative Example 1 15 Comparative Example 2 80 Comparative Example 3 75 Comparative Example 4 72 Comparative Example 5 76 Comparison example 100

[0163] It can be seen from Table 3 that the gate breaking phenomenon can be effectively avoided by introducing the resin into the coating agent solution to coat the silver wet powder.

[0164] From Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3, the broken fence in Comparative Example 1 has been reduced, but it still does not meet the requirements, indicating that the resin content is too little; although the resin content in Comparative Example 2 is sufficient, after adding too much, the viscosity is too high, the printing is very poor, so the broken fence will also increase. The control example is to add acrylic resin during the slurry preparation process. Although this method reduces 3M shedding, the broken fence is aggravated. Acrylic resin can improve adhesion, but if it is added during the slurry preparation process, the slurry printing performance is worse.

[0165] In summary, by introducing a resin with high adhesion in the process of preparing silver powder and using the resin as a coating agent component, the adhesion of the TOPCon back-side fine grid paste after printing on the silicon wafer can be improved, avoiding the phenomenon of grid line falling off of the back-side paste. At the same time, it can ensure that the viscosity of the paste is low, improve printing smoothness, and avoid the problem of a large number of broken grids during the printing process.

[0166] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing silver powder, characterized in that: The following steps are involved: The silver ion solution, the reducing solution and the dispersant solution are mixed and reacted to obtain a reaction solution; the reaction solution is solid-liquid separated and the solid is collected; mixing the solid with a coating agent solution and drying; The coating agent solution includes a first solute and a second solute, wherein the first solute includes at least one of lauric acid, sodium laurate, a silane coupling agent, oleic acid, lauric acid, stearic acid, palmitic acid and benzotriazole; and the second solute includes at least one of acrylic resin, rosin resin and polyvinyl butyral resin; Preferably, the second solute is at least one of thermoplastic acrylate, hydrogenated rosin resin and polyvinyl butyral resin.

2. The preparation method according to claim 1, characterized in that: In the coating agent solution, the content of the first solute is 0.01 g / mL to 0.05 g / mL, and the content of the second solute is 0.01 g / mL to 0.05 g / mL; Preferably, in the coating agent solution, the solvent includes at least one of ethanol, isopropanol and acetone.

3. The preparation method according to claim 1, characterized in that: The concentration of silver ions in the silver ion solution is 0.1 mol / L to 5 mol / L; Preferably, the concentration of silver ions in the silver ion solution is 0.5 mol / L to 3 mol / L; Preferably, the silver ion solution is obtained by mixing silver nitrate and water.

4. The preparation method according to claim 1, characterized in that: The concentration of the reducing agent in the reducing solution is 0.2 mol / L to 2 mol / L; Preferably, the concentration of the reducing agent in the reducing solution is 0.4 mol / L to 1.5 mol / L; Preferably, the reducing agent comprises at least one of glucose, hydrazine hydrate, sodium borohydride, potassium borohydride, ascorbic acid, urea, formaldehyde and isoascorbic acid.

5. The preparation method according to claim 1, characterized in that: The content of the dispersant in the dispersant solution is 0.01 g / mL to 1 g / mL; Preferably, the content of the dispersant in the dispersant solution is 0.05 g / mL to 0.5 g / mL; Preferably, the dispersant in the dispersant solution includes at least one of polyvinyl pyrrolidone, maleic acid, cyclodextrin, fumaric acid, gelatin, malic acid, gum arabic, polyacrylamide and oleic acid.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The reaction temperature of the silver ion solution, the reducing solution and the dispersant solution is 15°C to 50°C, and the reaction time is 5min to 20min; The molar ratio of the reducing agent in the reducing solution to the silver ions in the silver ion solution is 0.5:1 to 4:1, and the mass of the dispersant in the dispersant solution is 1% to 40% of the mass of the silver source providing silver ions in the silver ion solution; Preferably, the molar ratio of the reducing agent in the reducing solution to the silver ions in the silver ion solution is 0.5:1 to 2:1, and the mass of the dispersant in the dispersant solution is 10% to 30% of the mass of the silver source providing silver ions in the silver ion solution; Preferably, the silver ion solution and the reducing solution are both introduced into the dispersant solution at a flow rate of 5 mL / min to 50 mL / min; Preferably, the reaction is carried out at a stirring speed of 200 rpm to 250 rpm.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the solid to the coating agent solution is 1:1 to 1:2; and / or, the solid and the coating agent solution are mixed at a stirring speed of 100 rpm to 800 rpm for 5 min to 60 min; and / or, the drying temperature after the solid and the coating agent solution are mixed is 35° C. to 60° C., and the drying time is 1 h to 5 h; Preferably, before mixing with the coating agent solution, the solid is further washed; Preferably, the solid is washed with deionized water and ethanol in sequence until the conductivity of the washing liquid is ≤20 μs / cm.

8. A silver powder, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7; Preferably, the silver powder has a D 50 1.2μm~1.8μm; Preferably, the tap density of the silver powder is 5.5 g / cm 3 ~6.3g / cm 3 ; Preferably, the specific surface area of ​​the silver powder is 0.35 m 2 / g~0.75m 2 / g; Preferably, the burnout of the silver powder is 0.5wt% to 1wt%.

9. A silver paste, characterized in that: The raw materials for preparing the silver paste include an organic carrier, glass powder and the silver powder according to claim 8; Preferably, in parts by weight, the raw materials for preparing the silver paste include 86 to 90 parts of the silver powder, 8 to 12 parts of the organic vehicle and 2 to 3 parts of the glass powder.

10. A TOPCon battery, characterized in that: The silver paste on the back side of the TOPCon battery is the silver paste described in claim 9.

Citation Information

Patent Citations

  • Electrode silver paste for front surface of crystalline silicon solar cell

    CN113871056A

  • Low-temperature quick-drying mask silver paste for intaglio printing and preparation method thereof

    CN114864132A

  • Micro-nano silver dispersion and preparation method thereof

    CN115673334A

  • Preparation method of silver powder with adjustable sintering activity

    CN116984621A

  • Silver-aluminum paste, preparation method thereof and application of silver-aluminum paste in preparation of N-topcon solar cell

    CN117174356A